Weaning age in an expanding population: stable carbon and nitrogen isotope analysis of infant feeding practices in the Okhotsk culture (5th–13th centuries AD) in Northern Japan. Issue 4 (27th March 2015) - Tsutaya, Takumi; Ishida, Hajime; Yoneda, Minoru
ABSTRACT Objective: The Okhotsk people were sedentary hunter–gatherer–fishers who lived and prospered in Sakhalin, Hokkaido, and the Kurile Islands during the 5th to 13th centuries AD. They expanded rapidly along the northeastern coast of Hokkaido. We reconstructed infant feeding practices of the Moyoro population of the Okhotsk culture in eastern Hokkaido, Japan. Methods: Stable isotope ratios in 58 subadult human skeletons were measured. Results: The results suggest that complementary foods with a relatively low carbon isotope ratio were consumed during and after weaning, as observed in ethnographic descriptions of northern human populations such as the Ainu and isotopically suggested in ancient northern hunter–gatherer–fisher populations. Nitrogen isotope ratios of subadults showed that the age at the end of weaning in the Moyoro population was 1.8 (1.4–2.2 in 95% credible interval) years, which is earlier than that in other northern hunter–gatherer–fisher populations. Conclusions: Because weaning age is one of the most important determinants of fertility, a shorter breastfeeding period suggests increased fertility. Furthermore, better nutrition would further promote the population increase, and thus populations of the Okhotsk culture could expand into new regions. These findings are consistent with recent emerging evidence of great contributions of the Okhotsk to the formation of later Ainu populations and culture. Am J Phys Anthropol 157:544–555, 2015. © 2015 Wiley Periodicals, Inc.